2010
DOI: 10.7196/samj.3952
|View full text |Cite
|
Sign up to set email alerts
|

Differences in access and patient outcomes across antiretroviral treatment clinics in the Free State province: A prospective cohort study

Abstract: Objective. To assess differences in access to antiretroviral treatment (ART) and patient outcomes across public sector treatment facilities in the Free State province, South Africa.Design. Prospective cohort study with retrospective database linkage. We analysed data on patients enrolled in the treatment programme across 36 facilities between May 2004 and December 2007, and assessed percentage initiating ART and percentage dead at 1 year after enrolment. Multivariable logistic regression was used to estimate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…4,6 Further motivation to rapidly improve access is evidence showing that more than 80% of deaths during the first year after diagnosis of HIV infection occurred before these patients could be started on ART. 7 Because of the need to scale-up access to ART, President Zuma announced on World AIDS Day, 1 December 2009, that any citizen would be able to access counselling, testing and treatment at any health centre. 8 This meant increasing the number of sites providing ART from 496 to 4 333.…”
mentioning
confidence: 99%
“…4,6 Further motivation to rapidly improve access is evidence showing that more than 80% of deaths during the first year after diagnosis of HIV infection occurred before these patients could be started on ART. 7 Because of the need to scale-up access to ART, President Zuma announced on World AIDS Day, 1 December 2009, that any citizen would be able to access counselling, testing and treatment at any health centre. 8 This meant increasing the number of sites providing ART from 496 to 4 333.…”
mentioning
confidence: 99%
“…In this study, although no statistically significant factors associated with retention in pre-ART care were found, the odds ratios suggested that females and those knowing someone on ART were more likely to be retained in pre-ART care. Likewise, a range of factors associated with retention in or loss to pre-ART care have been described in other studies [6], [11], [12], [23], [24]. In a study in KwaZulu -Natal retention in pre-ART care was associated with female sex as well as a lower initial CD4 count and older age [12].…”
Section: Discussionmentioning
confidence: 70%
“…In a study in KwaZulu -Natal retention in pre-ART care was associated with female sex as well as a lower initial CD4 count and older age [12]. Factors influencing loss to pre-ART care included distance from the health centre [6], [11] male sex [6], [11], [23] a low CD4 count [6], [11] a history of being treated for TB, referral for HIV testing by a health care provider as opposed to self-referral, weight below 50 kg, unemployment [11] and younger age [23]. A qualitative study, as part of the researching equity in access to healthcare (REACH) project, found that continuing adherence to ART was positively affected by social and economic support by families, friends and the broader community, and negatively by transport and food costs [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations